Inequality of educational opportunity at time of schooling predicts cognitive functioning in later adulthood - Anja K. Leist; Eyal Bar-Haim; Louis Chauvel (Elsevier, 2021)
Objectives: Our understanding of how societal conditions and educational policies influence cognitive development across the life course is improving. We tested the extent to which inequality of educational opportunity (IEO), the country- and cohort-specific correlation of parents' and their offspring's length of schooling, offers systematically different opportunities to contribute to cognitive development, which in turn influences cognitive abilities up to older ages. Methods: A total of 46,972 individuals of three cohorts born 1940-63 from 16 European countries and Israel provided up to six cognitive assessments and information on covariates in the SHARE survey 2004-2017. Individual-level data were linked to indicators of IEO at time of schooling, and economic, health, and human development, provided by World Bank, WHO, and the UN. Results: In multilevel (mixed-effects) models with random individual and country-cohort effects and adjusted for a large set of confounders, higher IEO was associated with lower levels of cognitive functioning in men and women. Interaction analyses suggested lower cognitive levels particularly of women who were schooled in higher IEO contexts and had lower educational attainment. Associations with rate of change in cognitive functioning were present only in women, however there was little clinically relevant cognitive decline across the window of observation. Result patterns were mostly consistent after including additional contextual indicators, and in a subsample with childhood information. Discussion: Findings suggest that IEO is able to substantially influence cognitive development with long-lasting impacts. Lower-educated women of the cohorts under investigation may have been particularly vulnerable to high-inequality educational contexts.